Capital, class and the social necessity of passenger air transport. (October 2020) - Young, Martin
The symbiotic, environmentally destructive relationship between passenger air transport and economic output remains inadequately theorised by both transport geographers and mobilities researchers. This article attempts to bridge the two fields by considering passenger air transport as a branch of value production whose useful effect – the movement of people across space – is a 'connecting artery' necessary to multiple consumption and production processes. Air travel is socially necessary to multiple class projects, including the reproduction of labour power, the competitive reorganisation of capital at the global scale, and the consolidation of transnational capitalist class power. A corresponding environmental politics of resistance is outlined.